E-PURCHASING KATALOG ELEKTRONIK DAN KOMPETENSI PEGAWAI DALAM PROSES PENGADAAN BARANG DAN JASA TERHADAP KEPUASAN PELAYANAN PUBLIK - Hakim, Adi Lukman; Basyah, Muhammad Ali; Rosiawan, Rizky Wahyudha; Utama, Andi Putra (STIE Mahardhika, 2025)
This study aims to determine the effect of the implementation of e-Purchasing Electronic Catalogues and employee competence in the procurement process of goods and services on public service satisfaction at the Lamongan District Education Office. This study uses a quantitative approach with a survey method. The research sample consisted of 105 respondents, including procurement officials, school principals, and procurement-related staff at the Lamongan District Education Office, selected using purposive sampling techniques. The research instrument used a closed questionnaire with a Likert scale. The data analysis technique used was multiple linear regression to test the partial and simultaneous effects between variables. The results showed that, partially, both the implementation of e-Purchasing and employee competence had a significant effect on public service satisfaction. Simultaneously, both independent variables also had a significant effect on public service satisfaction